A new constitutive equation to predict single peak flow stress curves at high temperatures: a comprehensive study on different steels. (2nd January 2017) - Shafiei, E.; Goodarzi, N.; Dehghani, K.; Soltani Tehrani, A.
ABSTRACT: In this study, a new constitutive equation, using the extrapolation of dynamic recovery (DRV) flow stress curve and Avrami kinetics equation for dynamic recrystallisation (DRX), has been developed. The dynamic recovery flow stress curves pertaining to unrecrystallised regions were extrapolated based on a non-linear estimation of strain hardening rate versus strain. The critical strain ( ) for the initiation of DRX was determined utilising flow stress curve modelling up to the peak. In order to verify the accuracy of the model, nineteen flow stress curves under DRX conditions on 7 different steels were analysed. The proposed constitutive model correlates well with experimental results, which confirms that the proposed model can give a precise estimation of flow stress curves.